2004
DOI: 10.1021/ac0493830
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Flow Control Concept for Single-Cell Experiments on a Microchip. 2. Fluorescein Diacetate Metabolism and Calcium Mobilization in a Single Yeast Cell As Stimulated by Glucose and pH Changes

Abstract: Using a three-dimensional flow control concept to manipulate and retain a single yeast cell in a microchip, we were able to study the kinetics of intracellular metabolism and calcium mobilization at the single-cell level, as stimulated by glucose and pH changes. As a model study, the fluorogenic substrate fluorescein diacetate (FDA) was chosen to study how the intracellular carboxylesterase metabolize it. A single yeast cell was first cultured in the microchip. Thereafter, under a constant concentration of FDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…When ionomycin permeated into CHO cells it caused cells to release Ca 21 from internal stores into the cytosol and the released Ca 21 would quickly combine with the calcium indicator, Fluo-4 AM. The reason for the signal decline following its maximum is unclear, although it is possible that an efflux of Ca 21 and/or the calcium indicator from the cell may occur, which in turn will reduce the fluorescent signal observed in the cell [36].…”
Section: In Situ Monitoring Of Calcium Flux Responsementioning
confidence: 99%
“…When ionomycin permeated into CHO cells it caused cells to release Ca 21 from internal stores into the cytosol and the released Ca 21 would quickly combine with the calcium indicator, Fluo-4 AM. The reason for the signal decline following its maximum is unclear, although it is possible that an efflux of Ca 21 and/or the calcium indicator from the cell may occur, which in turn will reduce the fluorescent signal observed in the cell [36].…”
Section: In Situ Monitoring Of Calcium Flux Responsementioning
confidence: 99%
“…Peng et al reported a PDMS-based microfluidic device for the detection of intracellular calcium mobilization and fluorescein diacetate (FDA) at single-cell level. In their work, the variation of PH and glucose and the retaining of single cells within microchannels were all controlled by 3D liquid flow [ 104 , 105 ]. They further developed a CD-like microfluidic device with spiral microchannels for DNA hybridizations under similar principle and manipulation [ 106 ].…”
Section: The Application Of Polymer-based Microfluidics For Singlementioning
confidence: 99%
“…Previously, a single yeast cell cultivation system using a microchamber array had not been reported because the small amount of medium in the microscale cultivation dried up. In a different type of system, another yeast cell cultivation system was also reported [129,130], which involved a liquid flow channel system with a small tank within a modified glass slide for the cocultivation of a number of yeast cells. The purpose of the system was to observe cell cycles and the fluorescence of cells within a small cultivation bath.…”
Section: Devices For Functional Analysis Of Pro-teins Produced By Molmentioning
confidence: 99%